Yersinia enterocolitica: a rare cause of infected aortic aneurysm successfully treated with antibiotics and endovascular repair. Issue 2 (June 2014) - Kumar, Prashant; Zhang, John; Miller, Sarah; Wilton, Gavin
Abstract : Introduction: Yersinia enterocolitica is a Gram‐negative coccobacillus belonging to the family Enterobacteriaceae . We present a rare case of abdominal aortic aneurysm infected with Y. enterocolitica that was successfully managed using intravenous antibiotics and endovascular aneurysm repair. Case presentation: A 74‐year‐old male was admitted with a 1‐week history of feeling generally unwell with worsening abdominal pain radiating through to his back. Inflammatory markers were raised and blood cultures grew Y. enterocolitica biotype 2. A computed topography scan revealed a 50 mm infected abdominal aortic aneurysm. The patient was successfully treated with intravenous antibiotics and endovascular aneurysm repair. Conclusion: Whilst endovascular aneurysm repair has been increasingly used to treat aortic aneurysms infected with a variety of pathogens, this is, to our knowledge, the first reported case of an aortic aneurysm infected with Y. enterocolitica being treated by such a technique. Further research is required to establish the long‐term outcomes of patients undergoing endovascular repair of infected aneurysms.